Lost on the Silk Road: online drug distribution and the ‘cryptomarket’ - Martin, James (Criminology & criminal justice, 2014)
The illicit drugs website, Silk Road, presents an ideal case study for how online communication technologies are transforming crime. This article seeks to locate the offences committed via Silk Road within existing cybercrime literature, and presents a new criminological concept – the cryptomarket – to outline the contours of this new generation of online illicit marketplace. Cryptomarkets are defined as a type of website that employs advanced encryption to protect the anonymity of users. The article also analyses the implications Silk Road has for drug consumers and law enforcement, as well as the potential changes to drug distribution networks that are likely to occur if Silk Road and other cryptomarkets continue to assume a greater share of the global trade in illicit drugs. In conclusion, it is argued that while Silk Road presents a less violent alternative to conventional drug distribution networks, the risks posed by the rapid proliferation of cryptomarkets more generally are largely unknown and require further research.